Best practice guidelines for the measurement of physical activity levels in stroke survivors: a secondary analysis of an observational study. Issue 1 (March 2018) - Tinlin, Louise; Fini, Natalie; Bernhardt, Julie; Lewis, Lucy K.; Olds, Tim; English, Coralie
Abstract : The aim of this study was to investigate the phenomenon of activity (increased activity in response to monitor wear) and determine the minimum wear time of accelerometers when objectively measuring habitual physical activity levels of community dwelling stroke survivors. Exploratory, secondary analyses of cross-sectional data were carried out. Physical activity variables [sitting, standing and stepping time, step count, light physical activity and moderate-to-vigorous physical activity (MVPA)] were measured with two activity monitors for 7 days. Repeated-measures analysis of variance was used to assess reactivity. Minimum wear time was assessed using regression analyses and median absolute differences. Paired t -tests were used to assess differences between weekend and weekday activity levels. There was no evidence of reactivity. Minimum wear time was 3 days for all activity variables, with the exception of MVPA, for which 7 days of monitoring was required. There were no significant differences in weekend and weekday activity levels. To accurately measure activity levels of individuals with stroke, we recommend 3 days of monitoring for all activity variables, with the exception of MVPA, which requires 7 days.